Penggunaan Citra Radar Interferometri Untuk Pembuatan Peta Basis = The Use Of Interferometric Radar Imagery For Basic Map Making - Perpustakaan UGM, i-lib ([Yogyakarta] : Lembaga Penelitian dan Pangabdian kepada Masyarakat, Universitas Gadjah Mada, 1999)
ABSTRACT The preparation of national base map has been photogrametrically conducted. The use of this technology will, however, face an obstacle in the mountainous and cloudy area. The problem of cloud covering can be solved using the technology of Real Aperture Radar (RAR) or Synthetic Aperture Radar (SAR). These technologies still, however, face the obstacle of resolution, planimetrical error difficulties in height information extraction. The technology of Interferometric Synthetic Aperture Radar (Insar) uses two antennas to receive bounce back signal form certain object on the earth surface. Using the two antennas, two data phases will be obtained that subsequently show the phase differences between the object-antenna I and the object-antenna II at the same time. With the Integrated Data Language (IDL) software, insar image can be processed into Digital Elevation Model (DEM) and mosaic and contour map also can be made. In preparing the base map with the Insar technique, the problem of planimetrical position can be solved using Differential Global Positioning System (DGPS) technology that is operated together while imaging. The objects as planimetrical details in mapping, are extracted from the Insar image using interpretation technique. The planimetrical map is digitized using AutoCAD-13 software in order to be joined and stacked using contour map into base map of two scales, viz. 1:25.000 and 1:50.000. To know whether the obtained base map has met cartographical requirements or not, the comparison test is conducted using topographical map of 1:50.000 in scale and field test. Based on the result of the test and the analysis it can be concluded that: there is still a little doubt in the result for the mountainous area, while the result for the undulating and flat areas have met the cartographical requirements.